Developing an Intervention and Evaluation Model of Outdoor Therapy for Employee Burnout: Unraveling the Interplay Between Context, Processes, and Outcomes - Pijpker, Roald; Veen, Esther J.; Vaandrager, Lenneke; Koelen, Maria; Bauer, Georg F. (Frontiers in Psychology, 2022)
Background: Burnout is a major societal issue adversely affecting employees’ health and performance, which over time results in high sick-leave costs for organizations. Traditional rehabilitation therapies show suboptimal effects on reducing burnout and the return to work process. Based on the health-promoting effects of nature, taking clients outdoors into nature is increasingly being used as a complementary approach to traditional therapies, and evidence of their effectiveness is growing. Theories explaining how the combination of general psychological support and outdoor-specific elements can trigger the rehabilitation process in outdoor therapy are often lacking however, impeding its systematic research. Aim: The study aims to develop an intervention and evaluation model for outdoor therapy to understand and empirically evaluate whether and how such an outdoor intervention may work for rehabilitation after burnout. Methodological approach: We build on the exemplary case of an outdoor intervention for rehabilitation after burnout, developed by outdoor clinical psychologists in the Netherlands. We combined the generic context, process, and outcome evaluation model and the burnout-recovery model as an overarching deductive frame. We then inductively specified the intervention and evaluation model of outdoor therapy, building on the following qualitative data: semi-structured interviews with outdoor clinical psychologists and former clients; a content analysis of the intervention protocol; and reflective meetings with the intervention developers and health-promotion experts. Results: We identified six key outdoor-intervention elements: 1) physical activity; 2) reconnecting body and mind; 3) nature metaphors; 4) creating relationships; 5) observing natural interactions; and 6) experiential learning. The results further showed that the implementation of these elements may facilitate the rehabilitation process after burnout in which proximal, intermediate, and distal outcomes emerge. Finally, the results suggested that this implementation process depends on the context of the therapist (e.g., number of clients per day), therapy (e.g., privacy issues), and of the clients (e.g., affinity to nature). Conclusion: The intervention and evaluation model for outdoor therapy shows how key outdoor intervention elements may contribute to the rehabilitation process after burnout. However, our model needs to be further tested among a larger group of clients to empirically evaluate whether and how outdoor therapy can support rehabilitation.